A HISTORICAL PERSPECTIVE ON THE DEVELOPMENT OF GREEN CONSUMER BEHAVIOR - prabowo, faizal haris eko; Herlina, Elin; Mutmainnah, Indy Insanul; Gacuma, Leah Rose D (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
With the emergence of a campaign on sustainable development carried out by the UN, this movement stimulates all communities to practice environmental preservation activities. The purpose of research is to analyze the theoretical development of green consumer behavior. Increasing problems and issues regarding environmental sustainability every decade continue to be the main focus of many parties. The theory of green business continues to develop and gives rise to many derivatives. The difference in this study is it summarizes and explains the development of theories regarding green consumer behavior. The method used in this research is literature review. The number of articles used as samples was 52 articles discussing green consumer behavior from various journal sources. It was found that the theory of green consumer behavior continues to develop over time. From these developments, five similar research categories were found, including: factors influencing green consumers, characteristics of green consumers, the cost of becoming a green consumer, the point of view of green consumers and the impact of green consumer behavior. The green consumer theory is one of the theories of green marketing that was also born from the green economy, where this theory is a conservation of the social humanities sector